1993
DOI: 10.1016/s0022-5347(17)35647-1
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Vesicle Parameters at 10-Year Intervals Measured by Transrectal Ultrasonography

Abstract: The volume, maximum horizontal area, maximum length, maximum width and depth of the seminal vesicles were measured by transrectal ultrasonography in 76 subjects without seminal vesicle disorders, divided into 7 groups at 10-year intervals. The average of each parameter in each group was presented. The volume and maximum horizontal area began to decrease after the age of 60 years. No statistically significant difference among subject ages was observed for the other 3 parameters. A correlation was observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Accordingly, we did not find any association between sperm parameters and SV volume or ejection fraction. SV diameters measured in our study were essentially in agreement with previously reported sonographic data (Fuse et al, 1992;Terasaki et al, 1993;Kim and Lipshultz, 1996;Colpi et al, 1997;La Vignera et al, 1998;Kim et al, 2009). However, the volume we derived was substantially lower than in previous studies (Tanahashi et al, 1975;Terasaki et al, 1993), probably because the mathematical model we used was different.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, we did not find any association between sperm parameters and SV volume or ejection fraction. SV diameters measured in our study were essentially in agreement with previously reported sonographic data (Fuse et al, 1992;Terasaki et al, 1993;Kim and Lipshultz, 1996;Colpi et al, 1997;La Vignera et al, 1998;Kim et al, 2009). However, the volume we derived was substantially lower than in previous studies (Tanahashi et al, 1975;Terasaki et al, 1993), probably because the mathematical model we used was different.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, SV volume has only been assessed in a few studies, in a limited series of subjects, using different algorithms and before ejaculation (Tanahashi et al, 1975;Terasaki et al, 1993). In addition, the few studies performed before and after ejaculation did not assess the SV volume, evaluating only SV anterior -posterior diameter (Colpi et al, 1997;La Vignera et al, 2008) or anterior -posterior and longitudinal diameter (Hernandez et al, 1990;Fuse et al, 1992;Terasaki et al, 1993). Finally, only some authors (Colpi et al, 1997;La Vignera et al, 2008) took sexual abstinence into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Stepwise multiple linear, logistic binary or ordinal regressions were applied for multivariate analysis whenever appropriate. As prostate and SV characteristics are strictly related to age and TT (see Morales, and Parsons et al ., ; for prostate; Terasaki et al ., ; Kim et al ., ; Lotti et al ., for SV) and prostate features can also be modulated by abdominal adiposity (Parsons et al ., , ; Lotti et al ., ), all data have been adjusted for age, TT and waist, unless otherwise specified. For graphic purpose, the NIH‐CPSI total score is reported on the abscissa as quartiles, although statistical analyses have been performed using the total score as a continuous variable.…”
Section: Methodsmentioning
confidence: 99%
“…As prostate and SV characteristics are strictly related to age and TT (see Morales, and Parsons et al ., for prostate; Terasaki et al ., ; Kim et al ., and Lotti et al ., for SV), and owing to the wide age range (18–61 years) and to the fact that sexual dysfunctions are age‐ and TT‐dependent phenomena (Lewis et al ., ), data have been adjusted for age and TT, unless otherwise specified. In addition, as thyroid function plays a role in modulating PRL (Melmed et al ., ) and sexual function (Corona et al ., ), data have been adjusted also for TSH, unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%